TONING DOWN OR ADAPTATION? A STUDY OF ENGLISH-INDONESIAN TRANSLATION ON AN ONLINE STREAMING PLATFORM - Indra Nugraha (EJI (English Journal of Indragiri) : Studies in Education, Literature, and Linguistics, 2023)
The study of translation remains an exciting field for language and linguistics experts. Its process involves many factors to consider. For example, the translation process for films' subtitles must consider the broadcasting regulations. Furthermore, the translation process will be more complicated if it involves a cultural-specific concept such as swearing. Theoretically, adaptation is used to translate a cultural-specific concept, and since swearing is one, adaptation should be applied. However, this method might not be ideal for translating swearing in films. This study was descriptive-qualitative research with a recording technique. Twenty data on English-Indonesian swearing were collected from two American films on an online streaming platform in Indonesia. The results show that eight data used a toning down strategy to acceptable words/expressions, seven were adapted, 4 data were omitted, and one used an unrelated word